TINJAUAN YURIDIS TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Eko Hariyanto (Ensiklopedia Education Review, 2022)
Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia determines that Indonesia is a country based on law. To realize these ideals, the entire community and institutions that play an important role in the Unitary State of the Republic of Indonesia must work hard, because creating a rule of law that complies with legal principles is not easy. One of the important instruments in realizing a rule of law state is Legislation, because Legislation is an instrument which is a direct reference in law enforcement. Legislation is a reflection of the embodiment of the concept of a rule of law that has been promoted by the founders of the Unitary State of the Republic of Indonesia. Laws and regulations are needed by the people of Indonesia because these laws and regulations are rules that can guarantee life as a rule of law for all levels of society. The main purpose of forming laws and regulations is not only to create codification of the norms and values of life that have settled in people's lives but to create modifications or changes in people's lives.Keywords: Formation, Legislation, Indonesia.